2022
DOI: 10.1002/2688-8319.12162
|View full text |Cite
|
Sign up to set email alerts
|

An operational land cover and land cover change toolbox: processing open‐source data with open‐source software

Abstract: Accurate and up‐to‐date land cover maps are vital for underpinning evidence‐based landscape management decision‐making. However, the technical skills required to extract tailored information about land cover dynamics from these open‐access geospatial data often limit their use by those making landscape management decisions. Using Dartmoor National Park as an example, we demonstrate an open‐source toolkit which uses open‐source software (QGIS and RStudio) to process freely available Sentinel‐2 and public LiDAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 72 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…It is highly expected that this research will contribute to the development of GIS, and the management of data and information generated can help map Arabica coffee land development planning logically and sustainably to increase the income of coffee farmers and surrounding communities while increasing regional income. This also answers the importance of the chosen research location because the existing phenomenon that the higher the area, the lower the income level of farmers can be refuted [12][13][14][15].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is highly expected that this research will contribute to the development of GIS, and the management of data and information generated can help map Arabica coffee land development planning logically and sustainably to increase the income of coffee farmers and surrounding communities while increasing regional income. This also answers the importance of the chosen research location because the existing phenomenon that the higher the area, the lower the income level of farmers can be refuted [12][13][14][15].…”
Section: Introductionmentioning
confidence: 88%
“…2, used in field surveys to identify and inventory biophysical and non-biophysical environmental conditions so that data or parameters in geographical indication units can be separated appropriately and correctly. The technical skills required to extract information relevant to land cover dynamics from geospatial data [13].…”
Section: Problem Assessment and Literature Studymentioning
confidence: 99%
“…Finally, features known to result in false positives (via iterative examination of trial output data) were removed as a raster mask using other spatial land cover datasets, including mapping of buildings and scree/outcrop rock formations (Gatis et al, 2022). These features were buffered and co‐processed to autonomously remove these false positives from the finalized dataset (Figure 2‐G).…”
Section: Methodsmentioning
confidence: 99%
“…These areas form a contiguous landscape block covering more than 3800 km 2 . This extent has an elevation range between sea level and 621 meters and demonstrates a diversity of landscape character types and habitats including urban, intensively managed farmland, commercial forestry, primary travel corridors, and open upland moorland with blanket bog habitats (Gatis et al, 2022). As such, this area provides a sufficient breadth of land cover types to test the robustness of the mapped THaW habitats and the detection of canopy change.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we have demonstrated that Machine Learning LC annotation was able to efficiently scale to large areas; after training and testing on just over four square kilometres of LC image patches, we could predict the LC of 1439 km 2 of land within days on a desktop computer (Figure 8). Compared to the visual interpretation approach [9,10] or low-resolution automated LC maps [21], our method facilitates a range of new applications that require detailed knowledge of the landscape's land cover [53]. For example, these include fire risk modelling [8], climate change vulnerability assessments [4], tree planting planning [54], biodiversity monitoring [55,56] and habitat mapping [57][58][59].…”
Section: Land Cover Prediction Of a Uk National Parkmentioning
confidence: 99%